Students' Journals, A Source of Information for Assessment - Judith Castellanos Jaimes (Asociación Colombiana de Profesores de Ingles, 2016)
This article reports on a small-scale project conducted with first semester preservice students of an ELT teacher education program at Universidad Distrital during the first semester, 2004. This article explores the role of journals as a rich source of information for assessment. Assessment is understood as nonmeasurement (qualitative) techniques that provide information useful for instructional planning (Genesse and Upshur, 1999). The following two related questions guided this small-scale project: How can students' feedback inform my decision-making in ongoing instructional planning? What kinds of assessment information do students' journals provide? The findings concentrate on assessment information provided by students' journals by analyzing their weekly entries. The results suggest that valuing instructional activities, identifying language skills, strengths and weaknesses and students' experiences with language learning outside of school are the most frequent types of assessment information that constitute rich first-hand information for a teacher's decision-making in ongoing instructional planning.